All‐solid‐state Li‐ion batteries with commercially available electrolytes: A feasibility review - Rainer Götz; Raphael Streng; Johannes Sterzinger; Tim Steeger; Matti M. Kaye; Maksym Vitort; Aliaksandr S. Bandarenka (InfoMat)
Abstract The all‐solid‐state battery (ASSB) concept promises increases in energy density and safety; consequently recent research has focused on optimizing each component of an ideal fully solid battery. However, by doing so, one can also lose oversight of how significantly the individual components impact key parameters. Although this review presents a variety of materials, the included studies limit electrolyte‐separator choices to those that are either fully commercial or whose ingredients are readily available; their thicknesses are predefined by the manufacturer or the studies in which they are included. However, we nevertheless discuss both electrode materials. Apart from typical materials, the list of anode materials includes energy‐dense candidates, such as lithium metal, or anode‐free approaches that are already used in Li‐ion batteries. The cathode composition of an ASSB contains a fraction of the solid electrolyte, in addition to the active material and binders/plasticizers, to improve ionic conductivity. Apart from the general screening of reported composites, promising composite cathodes together with constant‐thickness separators and metallic lithium anodes are the basis for studying theoretically achievable gravimetric energy densities. The results suggest that procurable oxide electrolytes in the forms of thick pellets (>300 μm) are unable to surpass the performance of already commercially available Li‐ion batteries. All‐solid‐state cells are already capable of exceeding the performance of current batteries with energy densities of 250 Wh kg−1 by pairing composite cathodes with high mass loadings and using separators that are less than 150 μm thick, with even thinner electrolytes (20 μm) delivering more than 350 Wh kg−1.